A species radiation among South African flightless spring katydids (Orthoptera: Tettigoniidae: Phaneropterinae: Brinckiella Chopard) - Naskrecki, Piotr; Bazelet, Corinna S. (Zootaxa, 2009)
A previously unknown radiation among flightless spring katydids (Tettigoniidae: Phaneropterinae: Brinckiella) in Western and Northern Cape provinces of South Africa is described. Seven species are described as new (B. aptera n. sp., B. arboricola n. sp., B. elegans n. sp., B. karooensis n. sp., B. mauerbergerorum n. sp., B. serricauda n. sp., and B. wilsoni n. sp.) and one species (B. viridis Chopard) is redescribed.